The Last Kids on Earth - Book 1 - Brallier, Max; Holgate, Douglas (New York, New York : Viking, 2015)
"After a monster apocalypse hits town, average thirteen- year-old Jack Sullivan builds a team of friends to help slay the eerily intelligent monster known as Blarg"--
650L
Decoding demand: 86 (very high)
Semantic demand: 100 (very high)
Syntactic demand: 88 (very high)
Structure demand: 88 (very high)
Accelerated Reader AR
Keywords: Survival; Juvenile fiction; Monsters -- Juvenile fiction; Survival -- Fiction; Monsters -- Fiction; Friendship; Fiction